Dynamics and prognostic value of B-type natriuretic peptide in left ventricular assist device recipients - Papathanasiou, Maria; Pizanis, Nikolaus; Tsourelis, Loukas; Koch, Achim; Kamler, Markus; Rassaf, Tienush; Luedike, Peter (Journal of Thoracic Disease, 2018)
Background: The prognostic utility of B-type natriuretic peptide (BNP) in heart failure is well recognized. Previous studies demonstrated that BNP levels decrease after left ventricular assist device (LVAD) implantation. We sought to investigate the predictive value of baseline and changes in BNP levels in LVAD recipients. Methods: BNP was measured in baseline and follow-up plasma samples from consecutive patients receiving a continuous-flow LVAD from 2010 through 2016. Absolute values and changes from baseline were related to clinical outcomes. Results: Median BNP at baseline was 885 [interquartile range (IQR): 450–1,624] pg/mL, decreasing to 289 (IQR: 154–534) pg/mL at 90 days after LVAD implantation. Cox regression analysis revealed that higher baseline and follow-up BNP levels were not associated with increased risk of death at 180 days (P=0.12 and P=0.32, respectively). In the univariate analysis 90-day BNP, but not baseline BNP, was significantly associated with the combined death/hospitalization outcome 180 days after LVAD implantation [hazard ratio (HR) 1.03, 95% CI: 1.01–1.06; P=0.006]. This significance was not preserved after adjusting for multiple covariates (HR 1.01, 95% CI: 0.98–1.04; P=0.62). At 90 days, there was no BNP lowering in 20.6% of subjects. This was not associated with higher risk for death or the composite of death/hospitalization (P=0.11 and P=0.06 respectively). Conclusions: BNP absolute levels and changes from baseline are not independently associated with clinical outcomes after LVAD-implantation. These findings suggest an impaired prognostic performance of BNP after LVAD implantation.